Effect of wage-productivity gap on unemployment: evidence from emerging economies - Hafizah Sith; Hazrul Izuan Shahiri; Wye, Chung Khain; Zulkefly Abdul Karim (Penerbit Universiti Kebangsaan Malaysia, 2024)
The objectives of this study are to constructs the wage-productivity gap and its threshold effect on unemployment in emerging economies. The analysis involved the cross-section threshold regression method among 47 emerging economies from 2016 to 2018, where the Total Factor Productivity (TFP)/productivity is derived using the DEA Malmquist Productivity Index to generate the wage-productivity gap. The results demonstrate that as the wage-productivity gap widens and exceeds the negative threshold level with stronger productivity growth compared to wage growth, the unemployment rate rises. These results show that to keep the unemployment rate at the most manageable level, emerging economies must reduce the wage-productivity gap within the ideal range or threshold level. This gap is a significant indicator that impacts the unemployment rate and, consequently, contributes to enhancing workers’ productivity, income, and living standards.